Roll with it - Sumner, Jamie (Atheneum Books for Young Readers, 2019)
Twelve-year-old Ellie, who has cerebral palsy, finds her life transformed when she moves with her mother to small-town Oklahoma to help care for her grandfather, who has Alzheimer's Disease.